2019
DOI: 10.1101/683128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coevolutive, Evolutive and Stochastic Information in Protein-Protein Interactions

Abstract: Author contributions. WT designed research; MA and CP performed research; MA, CP and WT analyzed data; WT wrote original draft; WT, MA and CP reviewed and edited. MA and CP contributed equally to this work. ABSTRACTHere, we investigate the contributions of coevolutive, evolutive and stochastic information in determining protein-protein interactions (PPIs) based on primary sequences of two interacting protein families A and B . Specifically, under the assumption that coevolutive information is imprinted on the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Instead, these residues appeared to stabilize a specific loop conformation required for the peptide binding, by forming H-bonds within the CDRs. Accordingly, researchers have observed that residues that comprise the H-bond network within the TCR may be evolutionarily conserved [38,39] and that the internal organization of the interface plays an important role in proteinprotein interactions [40,41]. Our findings suggest that certain residues may be oriented in a specific direction with internal H-bonds and that the attention layer may emphasize their importance in TCRs in terms of binding stability.…”
Section: Interpretation Of Prediction In Protein Sequencesmentioning
confidence: 70%
“…Instead, these residues appeared to stabilize a specific loop conformation required for the peptide binding, by forming H-bonds within the CDRs. Accordingly, researchers have observed that residues that comprise the H-bond network within the TCR may be evolutionarily conserved [38,39] and that the internal organization of the interface plays an important role in proteinprotein interactions [40,41]. Our findings suggest that certain residues may be oriented in a specific direction with internal H-bonds and that the attention layer may emphasize their importance in TCRs in terms of binding stability.…”
Section: Interpretation Of Prediction In Protein Sequencesmentioning
confidence: 70%